Thermodynamic modelling of the binary indium-lithium system, a promising li-ion battery material - Gierlotka W.; Gąsior W.; Dębski A.; Zabrocki M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The binary In – Li system is a promising Li-ion battery anode material as well as a part of the important ternary Ge – In – Li system. The thermodynamic descriptions of metallic systems are widely used to retrieve information necessary for alloy applications. In this work, a thermodynamic model of a binary indium – lithium system prepared by the Calphad approach is proposed. The liquid phase was described by an associate model, and the solid phases determined by the ab-initio calculation were included in the thermodynamic modeling. The obtained set of self-consistent thermodynamic parameters well reproduces the available experimental data and enables further calculations of multi-component systems. A good agreement between the calculations and the available experimental data was found. The proposed model can be used for further descriptions of ternary systems.